Tradisi Kumpolan Di Desa Tanah Abang Utara Kec. Tanah Abang Kab. Penukal Abab Lematang Ilir - Destri Windiastiti; Endang Rochmiatun; Padila (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2024)
This research explains the Kumpolan tradition in Tanah Abang Utara village, Tanah Abang subdistrict, Penukal Abab Lematang Ilir district. This study used qualitative research methods. A framework is needed to provide an explanation of the object of the main problem in more detail, the first main problem is how the Kumpolan traditional procession is in Tanah Abang Utara village, Tanah Abang subdistrict, Penukal Abab Lematang Ilir district. Second, what are the religious values contained in the Kumpolan tradition? This research uses religious value theory. The data sources used in this research are primary sources in the form of interviews with traditional leaders, village heads, traders and so on as well as secondary sources in the form of theses, journals and books related to this research.The results of the university's research show that the Kumpolan tradition was first formed from the habit of people who like to gather together while slaughtering buffalo, cows and goats, which was done during the Eid al-Adha and Eid al-Fitr holidays. It is on this day that all people carry out transactions. buying and selling meat from animals that have been slaughtered. This habit carried out by the people over time formed into a tradition which was named the Kumpolan tradition. The name Kumpolan itself was created according to the people's habit of often gathering, therefore the people gave the tradition the name Kumpolan which means gathering. As time goes by, currently the only animal used in Kumpolan traditional events is the Saia cow.